ALIRAN EKSISTENSIALISME DALAM PENDIDIKAN - Fanani, Arif (Institut Daarul Qur'an Jakarta, Indonesia, 2020)
Existentialism gives the individual a way of thinking about life, what it means to me, what is right for me. Existentialist epistomology holds that the individual is responsible for his own knowledge. The main source of knowledge is personal experience. The purpose of existentialism is to encourage each individual to be able to develop all his potential for self-fulfillment by providing a broad and comprehensive experience in all forms of life. The research method used in this research is the library method, namely by collecting information and data in depth through various literatures, books, notes, magazines, other references, as well as the results of previous relevant research. By applying the flow of existentialism in education, the hope is that it can make students realize that he himself has the responsibility to create his own meaning and definition